A Literature Review on Factors Affecting EFL Students’ Difficulties in Thesis Writing - Febriyanti, Eldis; Rugaiyah (English Education Department, 2025)
This study employs a literature review method that aims to investigate the factors affecting EFL students’ difficulties in writing their undergraduate theses. Writing a thesis in English poses numerous challenges for EFL learners, as it demands strong academic writing skills, sufficient language proficiency, and an understanding of research methodology. The purpose of this research is to identify three dominant categories of influencing factors: linguistic, psychological, and sociocultural. Data were collected by analyzing ten relevant journal articles retrieved from SciSpace, Consensus, and Google Scholar using the Publish or Perish application. The results show that linguistic limitations, psychological barriers such as anxiety and lack of motivation, and sociocultural challenges like insufficient academic support significantly contribute to students' struggles. These findings are expected to assist educators in creating more effective strategies and supportive environments to help EFL students succeed in thesis writing.